A comparison of the efficacy and side effects between 800mcg and 400mcg misoprostol in the management of missed miscarriages - Askandar Zulkarnaini, Nur Nadia (2015)

(untitled)
Introduction Misoprostol, a cheap and stable prostaglandin E1 analogue is the most widely studied drug for medical management of early pregnancy loss. In Malaysia, misoprostol is licensed for the management of stable first trimester miscarriages less than 13 weeks by Mesyuarat Panel Kaji Semula Senarai Ubat KKM. Most studies involving misoprostol compares between surgical and medical management of first trimester miscarriage. There is no study done comparing the doses of misoprostol in treatment of miscarriage available. This study compares between 400mcg and 800mcg in patient with uncomplicated missed miscarriage. Objectives To evaluate the effectiveness an and side effects profile of two different dosages of misoprostol Methodology A randomised controlled, equivalence study comparing 400 mcg and 800 mcg misoprostol pervaginally on an outpatient basis. The allocated dose was repeated the next day orally if clinically the products of conception had not been passed. Complete miscarriage was evaluated using two methods: ultrasound criteria on Day 7 and clinical criteria whereby pt having symptoms and sign that needed surgical management (ERPOC). Equivalence was demonstrated if the 95% confidence interval [CI] of the observed risk difference between the two doses for complete miscarriage lay between -15.0 and 15.0%. Differences in side effects were evaluated using patient-completed questionnaires. RESULTS 136 women were allocated to receive 400 mcg and 132 women to 800 mcg misoprostol for the management of missed miscarriage. The rate of induced complete miscarriage was equivalent using both ultrasound criteria and clinical criteria (95% CI, P = 0.352). Following the 400 mcg dose, the reported rate of fever was stastically lower (95% CI, p<0.001). Othe side effects also lower with diarhhoea (95% CI, p = 0.031), tiredness (95% CI, p = 0.002) and headache(95% CI, p = 0.042) Conclusion 400 mcg is as efficacious as 800mcg in inducing complete miscarriage. It also showed less side effect profile with significant less fever, diarrhoea, tiredness and headache.